Efectos de un programa de acondicionamiento muscular en la fuerza reactiva de extremidades inferiores de futbolistas profesionales de la ciudad de Barranquilla (2019)
The aim of this study was to determine the effects of a muscle conditioning program in the reactive force of the lower extremities of professional footballers in the city of Barranquilla. A quasi-experimental, exposure-response study is presented in a group of 21 players belonging to the payroll of Club Deportivo Atlético Junior F.C., anthropometric and functional characteristics associated with the saltability of soccer players were evaluated before and after a 10-week muscle conditioning program based on reactive strengthening exercises. The program was structured within the general athletic fitness program provided by the coaching staff and consisted of the progression of 3 exercises with consecutive jumps, with a minimum frequency of 2 sessions per week. The main results showed a statistically significant increase (p> 0.05) in unilateral vertical saltability and a significant reduction in functional asymmetries of the lower extremities. From the present research work it can be concluded that the intervention proposal prepared for 10 weeks had a positive impact on the increase of the general functional condition of the lower extremities and reduced the functional asymmetries between the lower extremities